Preparation of hybrid organic-inorganic materials based on a di-ureasil matrix doped with lithium bis(trifluoromethanesulfonyl)imide - Barbosa, P. C. (2008)
In this presentation we describe the preparation of solvent-free solid polymer electrolytes (SPEs) by the sol-gel route with the incorporation of controlled quantities of lithium bis(trifluoromethanesulfonyl) imide (LiTFSI) into the host matrix. The host framework of these xerogels, designated as di-ureasils and represented by d-U(900), contains oxyethylene oligomers with about 15 repeat units bonded at each end to a siliceous backbone through urea bridging links. Electrolytes were characterized by ionic conductivity measurements, cyclic voltammetry at a gold microelectrode and thermal analysis. The results obtained reveal that these hybrid materials are completely amorphous and exhibit appropriate electrochemical characteristics for a variety of applications.